Burkitt lymphoma: interpreting FISH testing for MYC gene rearrangements. Issue 2 (8th February 2022) - Sharma, Purva; Singal, Sakshi; Costello, Patrick; Krishnan, Koyamangalath
Abstract : Burkitt lymphoma is a highly aggressive B cell non-Hodgkin's lymphoma characterised by translocation of MYC gene on chromosome 8. This translocation is usually detected by fluorescent in-situ hybridisation (FISH) studies as part of routine diagnostic work-up and prognostication. FISH testing is commonly done with the break-apart probe (BAP). This case illustrates how this testing can be falsely negative. This patient is a young male diagnosed with Stage I low-risk Burkitt with FISH negative for MYC translocation initially on BAP testing. Additional testing with dual FISH probe detected MYC/IGH translocation. FISH testing using BAPs alone may be falsely negative for MYC translocations creating a diagnostic challenge and compromising the treatment approach and assessment of prognosis.